1986
DOI: 10.1037/0022-0167.33.2.190
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive assessment of social-evaluative anxiety in the job interview: Job Interview Self-Statement Schedule.

Abstract: The development of the Job Interview Self-Statement Schedule (JISSS), a device for the assessment of positive and negative cognitions that may occur during job-selection interviews, is described. Procedures for item generation, item selection, and subscale development are detailed, and preliminary normative, factor analytic, reliability, and validity data are reported. The JISSS appears to be an internally consistent and valid measure of cognitive activity during interview imagery. Positive and negative self-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…Several authors (Heimberg, Keller, & Peca-Baker, 1986;Kendall & Korgeski, 1979) have suggested the importance of including cognitive assessment measures in studies of cognitivebehavioral techniques. It is important to show that cognitive techniques result in changes on these measures.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors (Heimberg, Keller, & Peca-Baker, 1986;Kendall & Korgeski, 1979) have suggested the importance of including cognitive assessment measures in studies of cognitivebehavioral techniques. It is important to show that cognitive techniques result in changes on these measures.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of coping on adjustment has received a good deal of attention, with research on how people cope with marital problems (Menaghan, 1982), community living (McCrae & Costa, 1986), back pain (Rosenstiel & Keefe, 1983), donating blood (Kaloupek, White, & Wong, 1984), genital herpes (Manne & Sandler, 1984), abortion (Major, Mueller, & Hildebrandt, 1985), offensive behaviors (Barth, Schinke, & Maxwell, 1983), aging (Lazarus & DeLongis, 1983), test anxiety (Sarason, 1984), interview anxiety (Heimberg, Keller, & Peca-Baker, 1986), breast cancer (Taylor, 1983), rape (Janoff-Bulman, 1979), chronic illness (Felton & Revenson, 1984), and daily events (Folkman & Lazarus, 1980). The present study contributes to this Zeitgeist by adding to our understanding of several issues related to coping and depression.…”
Section: Discussionmentioning
confidence: 99%
“…A modified version of the NSS subscale of the Job Interview Self-Statement Schedule (Heimberg et al, 1986) was used to assess negative self-thoughts used by interviewees in the interview. The NSS sub-scale consisted of 25 items (e.g., 'This is stressful', 'I'm not expressing myself clearly').…”
Section: Negative Self-thoughtsmentioning
confidence: 99%